A chitosan supported peroxidovanadium(V) complex: Synthesis, characterization and application as an eco-compatible heterogeneous catalyst for selective sulfoxidation in water. (1st February 2019) - Saikia, Gangutri; Ahmed, Kabirun; Gogoi, Sandhya Rani; Sharma, Mitu; Talukdar, Hiya; Islam, Nashreen S.
Graphical abstract: A new chitosan immobilized peroxidovanadium complex served as water tolerant heterogeneous catalyst for the selective and sustainable oxidation of sulfides to sulfoxides in water. Abstract: Anchoring of peroxidovanadium(V) (pV) species to chitosan, a natural chelating polymer, afforded a new and structurally defined immobilized complex, VO(O2 )2 (NH2 )-chitosan (ChpV ) which was comprehensively characterized by elemental analysis (CHN, ICP-OES, energy dispersive X-ray spectroscopy), spectral studies (FT-IR, Raman, 13 C NMR, diffuse reflectance UV–Vis and XPS), SEM, XRD, Brunauer–Emmett–Teller (BET) and thermogravimetric analysis (TGA). Apart from being thermally stable, the compound is water-tolerant and non-hygroscopic. The compound effectively facilitated chemoselective oxidation of thioethers with H2 O2 in aqueous medium to the respective high purity sulfoxide, in impressive yield (TOF 5628 h −1 ) and with high H2 O2 efficiency, under mild reaction condition. In addition to water, the heterogeneous catalyst is highly compatible in a variety of organic solvents and is recyclable for several catalytic cycles without significant loss in selectivity. The catalytic procedure is amenable to ready scalability and is free from halogen, co-catalyst and acidic or any other hazardous additive.